2018
DOI: 10.3892/etm.2018.6640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atrial fibrillation on complications and prognosis of patients receiving emergency PCI after acute myocardial infarction

Abstract: The effects of atrial fibrillation on complications and prognosis of patients receiving emergency percutaneous coronary intervention after acute myocardial infarction (AMI) were investigated. Eighty AMI patients treated with interventional vascular recanalization in the Affiliated Hospital of Weifang Medical University (Weifang, China) from July 2015 to October 2016 were selected, including 40 patients complicated with atrial fibrillation before operation (control group) and 40 patients without atrial fibrilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
(19 reference statements)
0
11
0
1
Order By: Relevance
“…Four trials did not belong to RCTs ( Ye, 2019 ; Li, 2020 ; Wen and LYU, 2020 ; Zhao et al, 2022 ), three trials had duplicate data ( Luan, 2012 ; Pang, 2016 ; He and Wang, 2019 ), and another four trials did not include outcomes that met the criteria ( Lin, 2012 ; Mao et al, 2015a ; Mao et al, 2015b ; Zhou et al, 2016 ). Ultimately, 17 trials ( Du and Wang, 2011 ; Luan and Pan, 2012 ; Wu et al, 2015 ; He, 2016 ; Li, 2016 ; Chen et al, 2017 ; Lin et al, 2017 ; Du et al, 2018 ; Luo, 2018 ; Pang et al, 2019 ; Tao et al, 2019 ; Zhang and Jin, 2019 ; Lian, 2020 ; Lu et al, 2021 ; Mao et al, 2021 ; Zheng et al, 2021 ; Yu et al, 2022 ) were deemed qualified for the meta-analysis. The PRISMA flow chart of the trial selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four trials did not belong to RCTs ( Ye, 2019 ; Li, 2020 ; Wen and LYU, 2020 ; Zhao et al, 2022 ), three trials had duplicate data ( Luan, 2012 ; Pang, 2016 ; He and Wang, 2019 ), and another four trials did not include outcomes that met the criteria ( Lin, 2012 ; Mao et al, 2015a ; Mao et al, 2015b ; Zhou et al, 2016 ). Ultimately, 17 trials ( Du and Wang, 2011 ; Luan and Pan, 2012 ; Wu et al, 2015 ; He, 2016 ; Li, 2016 ; Chen et al, 2017 ; Lin et al, 2017 ; Du et al, 2018 ; Luo, 2018 ; Pang et al, 2019 ; Tao et al, 2019 ; Zhang and Jin, 2019 ; Lian, 2020 ; Lu et al, 2021 ; Mao et al, 2021 ; Zheng et al, 2021 ; Yu et al, 2022 ) were deemed qualified for the meta-analysis. The PRISMA flow chart of the trial selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported the results of inflammatory factors and vascular endothelial function in detail, among which the more commonly used indicators were analyzed. Ten trials (Du and Wang, 2011;He, 2016;Li, 2016;Du et al, 2018;Luo, 2018;Zhang and Jin, 2019;Lian, 2020;Lu et al, 2021;Mao et al, 2021; reported MACE information. In addition, ten trials reported adverse events, of which four (Chen et al, 2017;Lin et al, 2017;Luo, 2018;Tao et al, 2019) reported no adverse events and the remaining six (He, 2016;Li, 2016;Pang et al, 2019;Lian, 2020;Zheng et al, 2021; reported a total of 28 adverse events.…”
Section: All Research Interventions Included Sts In Combination Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Early percutaneous coronary intervention (PCI) can restore blood flow to ischemic myocardium, decrease infarct size, and reduce mortality and complications [1], but about 10-30% of patients exhibit no-reflow or slowreflow phenomena after PCI, which seriously affects prognosis [2]. The main cause of no-reflow or slow-reflow after PCI is coronary microembolism (CME) [3], resulting in myocardial cell necrosis and apoptosis, ventricular remodeling, malignant arrhythmia, and cardiac failure [4]. No drugs or mechanical devices are currently available to prevent CME, and remedial measures after the occurrence of CME have only a limited impact on the development of arrhythmias and prognosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…По данным исследований риск развития ФП у пациентов с острым инфарктом миокарда (ИМ) с подъемом сегмента ST (ИМпST) превышает 15% [4]. Известно, что ФП, возникшая во время ИМ, а также в раннем периоде после чрескожного коронарного вмешательства (ЧКВ), статистически значимо ухудшает прогноз выживаемости пациентов [5]. Данное обстоятельство, в первую очередь, обусловлено прогрессивным ухудшением кровоснабжения синоатриального узла, усугублением степени ишемии миокарда, развитием гипоксии и нарастанием сердечной недостаточности [6][7][8].…”
unclassified